A Csanád-monda = The legend of Csanad - Galambosi Péter (Belvedere Meridionale Szeged, 2021)
At the time of the state foundation, the territories southward from the river Maros were ruled by chief Ajtony, who disavowed the royal authority of king Saint Stephan. His story was told by the larger legend of Saint Gerrard and the gesta of the anonym notary of king Béla III. The fall of Ajtony was caused by the leader of his suite, Csanád, who had killed his superior, and then surrendered to King Stephan. Csanád got baptized and took part in the foundation of a diocese. In return, the king kept him in his position and didn’t cut up his territory into smaller administrative units.
Keywords: Bölcsészettudományok; Történettudomány és régészet